Orbital apex syndrome in a man with rhino-ocular cerebral mucormycosis: a case report - Kinza Moin; Aruba Mohsin; Humaid Sadiq; David Olukolade Alao (Journal of Medical Case Reports)
Abstract Background Orbital apex syndrome is a symptom complex of visual loss and ophthalmoplegia resulting from a disease involving the orbital apex. It can be caused by inflammation, infection, and malignancies. Mucormycosis is an infection caused by filamentous saprophytes of the order Mucorales. It is ubiquitous, and the infection can occur from ingesting contaminated food, inhaling spores, or injecting the disrupted skin or wounds. It is mainly a disease of the immunocompromised, affecting patients with poorly controlled diabetes, organ transplant recipients, and patients with hematological malignancies. We present the case of a man with orbital apex syndrome resulting from rapidly spreading rhino-ocular cerebral mucormycosis, who had a poor outcome despite an aggressive combined medical and surgical treatment. This is an unusual cause of orbital apex syndrome. Case presentation A 46-year-old Bangladeshi man presented to the emergency department with a history of toothache and pain in the left eye. On examination, the patient had a left-sided periorbital edema, ptosis, and proptosis. He had complete ophthalmoplegia and absent direct pupillary response in the left eye. Magnetic resonance imaging of the brain and orbit showed bilateral ethmoidal, left frontal, maxillary, and sphenoidal sinusitis with left orbital cellulitis. His left orbit was surgically decompressed and histology confirmed mucormycosis. Despite aggressive treatment, the patient had only a partial improvement in his symptoms. Conclusions Mucormycosis is a rare disease that can easily be misdiagnosed, leading to delayed treatment and disease dissemination. Clinicians must be suspicious of mucormycosis in patients presenting with multiple cranial nerve palsy.